Different rates of progression and mortality in patients with chronic kidney disease at outpatient nephrology clinics across Europe - Brück, Katharina; Brenner, Hermann (Kidney international, 2018)
The incidence of renal replacement therapy varies across countries. However, little is known about the epidemiology of chronic kidney disease (CKD) outcomes. Here we describe progression and mortality risk of patients with CKD but not on renal replacement therapy at outpatient nephrology clinics across Europe using individual data from nine CKD cohorts participating in the European CKD Burden Consortium. A joint model assessed the mean change in estimated glomerular filtration rate (eGFR) and mortality risk simultaneously, thereby accounting for mortality risk when estimating eGFR decline and vice versa, while also correcting for the measurement error in eGFR. Results were adjusted for important risk factors (baseline eGFR, age, sex, albuminuria, primary renal disease, diabetes, hypertension, obesity and smoking) in 27,771 patients from five countries. The adjusted mean annual eGFR decline varied from 0.77 (95% confidence interval 0.45, 1.08) ml/min/1.73m2 in the Belgium cohort to 2.43 (2.11, 2.75) ml/min/1.73m2 in the Spanish cohort. As compared to the Italian PIRP cohort, the adjusted mortality hazard ratio varied from 0.22 (0.11, 0.43) in the London LACKABO cohort to 1.30 (1.13, 1.49) in the English CRISIS cohort. These results suggest that the eGFR decline showed minor variation but mortality showed the most variation. Thus, different health care organization systems are potentially associated with differences in outcome of patients with CKD within Europe. These results can be used by policy makers to plan resources on a regional, national and European level.
Available online 12 April 2018
Gesehen am 27.06.2018